SOSIALISASI FIKIH MUAMALAT PRAKTIS DALAM KEHIDUPAN SEHARI-HARI: PENCEGAHAN JERATAN PINJOL DAN RIBA DI MASJID NURUL HILAL CENGKARENG - Hidayat (DEVELOPMENT: Journal of Community Engagement, 2022)
Cengkareng District, West Jakarta, as one of the most densely populated areas in DKI Jakarta, faces complex socio-economic challenges in the second decade of the 21st century. Modern financial phenomena, marked by the aggressive penetration of Financial Technology (Fintech), specifically Peer-to-Peer Lending (Pinjol) and Paylater features, have created new vulnerabilities among low and middle-income communities. Based on data from the 2019 National Survey of Financial Literacy and Inclusion (SNLIK) by the Financial Services Authority (OJK), there is a concerning gap between the national financial inclusion index reaching 76.19% and the sharia financial literacy index which remains stagnant at 8.93%. This disparity creates a void where the community accesses financial products without adequate understanding of risks and sharia compliance, resulting in widespread "robbing Peter to pay Paul" practices and entrapment in daily interest rates. This community service research, initiated by Dr. Hidayat, MA, aims to deconstruct conventional economic preaching approaches through the implementation of the Participatory Action Research (PAR) method. Located at Nurul Hilal Mosque, Kapuk Subdistrict, this research does not merely provide passive counseling but involves active community participation in four dialectical cycles: Mapping (To Know), Planning (To Plan), Action (To Act), and Reflection (To Reflect). The primary intervention focus is replacing theoretical and elitist fiqh contracts with applicable fundamental materials, namely the ontological distinction between Sale and Purchase (Bai') and Usury (Riba), as well as the ethics of Debts (Qardh) in the context of the digital economy. The results show that the PAR approach is effective in building the congregation's critical awareness. The Mapping Phase revealed that 70% of research subjects were unaware that late fees on Paylater applications are a form of contemporary jahiliyyah usury. The Planning Phase produced the "Anti-Default Fiqh" curriculum innovation which translates DSN-MUI Fatwas into market language. The Action Phase through the "Muamalah Clinic" successfully mediated the settlement of debt disputes amicably, while the Reflection Phase gave birth to social institutionalization in the form of the "Productive Infaq Movement" based on Ta'awun. This research concludes that the economic empowerment of the ummah cannot be conducted top-down but must grow from collective consciousness regarding the theological and sociological dangers of the usury system.